Phytoplankton Diversity as a Bioindicator for Water Quality of Pertamina Harbour Ampenan, Lombok - Ulfaturrahmi, Martina; Candri, Dining Aidil; Japa, Lalu; Ghazali, Mursal; Setyaningrum, Tri Wahyu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Ampenan district is an area that has a fairly high population density. There are community activities such as selling on the beach, littering, tourism activities and crossing activities at the Pertamina Harbour Ampenan which can cause a decrease in water quality. This research was conducted to determine water quality of Pertamina Harbour Ampenan based on phytoplankton community. Sea waters samplings were carried out using a 20µm plankton net. Observation and identification of phytoplankton was carried out in advances biology laboratory, FMIPA, Mataram University using a binocular microscope. Phytoplankton data were analyzed based on the abundance, diversity, dominance and saprobity index. The results of this research showed that the phytoplankton community of the Pertamina Harbour Ampenan waters consisted of 106 species from 6 classes with an abundance value of 4324,455 ind/L. Spesies diversity and dominant indexs of phytoplankton, and saprobic indexes of the Pertamina Harbour Ampenan waters were 1,767, 0,451 and 2,56 respectively. Based on the phytoplankton species diversity index, the waters of Pertamina Harbour Ampenan was categorized as moderately polluted, whereas saprobity index the waters of Pertamina Harbour was categorized as oligosaprobic.